Molecular Characterization of Animal Fasciola spp. Isolates from Kermanshah, Western Iran - Arezoo BOZORGOMID; Naser NAZARI; Hamzeh RAHIMI; Eshrat BEIGOM KIA; Homa HAJJARAN; Mehdi MOHEBALI; Mojgan ARYAEIPOUR; Peyman HEIDARIAN; Mohammad Saeid EZATI; Mohamad Bagher ROKNI (Tehran University of Medical Sciences, 2016)
Background: We evaluated the genetic diversity of samples identiﬁed morphologically as Fasciola spp. from sheep, cattle and goat from Kermanshah Province, western Iran using PCR-RFLP method. Methods: We used PCR-RFLP analysis of ribosomal ITS1 fragment using RsaI restriction enzyme to investigate the genetic characteristics of Fasciola species obtained from different hosts (16 sheep, 28 cattle, 4 goats). The species of Fasciola were confirmed by sequencing the 700 bp region of ribosomal ITS1 gene. Results: In Kermanshah, F. hepatica was present in 96% of the samples, F. gigantica was found only in two cattle sample. No hybrid forms were detected in the present study. Conclusion: Our results contribute to clarify the dark spots of Fasciola genotyping in different parts of Iran.   Keywords: Fasciola hepatica, Fasciola gigantica, Genotype, PCR, Iran